(untitled) (Educational Dimension, 2020)
In this article the author views philosophy questions of language and identity on bilingual education. There are two philosophies of bilingual education: maintenance and transitional, which influence on the way of learning foreign language and, as a result, on a person’s development in society — awareness of human identity. The author describes functions and structures of a bilinguism, a sociocultural competence, a language and an identity and says that learning languages and personality formation are connected. So that way what language and how we learning it define us in society.